Evaluating students engagement in classrooms using agent-based social simulation - Subramainan L.; Mahmoud M.A.; Ahmad M.S.; Yusoff M.Z.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Education; Education computing; Multi agent systems; Robotics; Surveys; Teaching; Agent based social simulation; Disciplinary actions; Emotional state; emotions; Engagement levels; Questionnaire surveys; Student engagement; Work in progress; Students